2023
DOI: 10.1101/2023.01.28.526021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

POLG genotype influences degree of mitochondrial dysfunction in iPSC derived neural progenitors, but not the parent iPSC or derived glia

Abstract: Diseases caused by POLG mutations are the most common form of mitochondrial disease and associated with phenotypes of varying severity. Clinical studies have shown that patients with compound heterozygous POLG mutations have a lower survival rate than patients with homozygous mutations, but the molecular mechanisms behind this remain unexplored. Using an induced pluripotent stem cell (iPSC) model, we investigate differences between homozygous and compound heterozygous genotypes in different cell types, includi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
3
4
0
Order By: Relevance
“…The current research identified a notable difference in the ability to restore mtDNA levels in iPSC‐derived NSCs carrying compound heterozygous POLG mutations, in comparison to both controls and homozygous mutation carriers. This discovery aligns well with the previous study, 38 which also highlighted a greater mitochondrial functional impairment in compound heterozygous NSCs compared to their homozygous counterparts. While both studies agree on the more severe impact of compound heterozygous POLG mutations in NSCs, it's intriguing to note the differences in manifestations across different cell types.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The current research identified a notable difference in the ability to restore mtDNA levels in iPSC‐derived NSCs carrying compound heterozygous POLG mutations, in comparison to both controls and homozygous mutation carriers. This discovery aligns well with the previous study, 38 which also highlighted a greater mitochondrial functional impairment in compound heterozygous NSCs compared to their homozygous counterparts. While both studies agree on the more severe impact of compound heterozygous POLG mutations in NSCs, it's intriguing to note the differences in manifestations across different cell types.…”
Section: Discussionsupporting
confidence: 92%
“…This therapeutic strategy might have broad implications, given the pervasive role of POLG in mitochondrial diseases. In conclusion, the observations from the present study and our previous paper 38 underline the complexity of the cellular response to POLG mutations, dependent not only on the type of mutation (homozygous or compound heterozygous) but also the specific cell lineage. These discoveries pave the way for more targeted therapeutic strategies.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations